Treatment of sludge incineration ash via sequential washing and chelation of heavy metals - Reva, Gupta (Nanyang Technological University, 2022)
Sewage sludge incineration generates sludge incineration ash (SIA). This by product is currently disposed in landfills. For a small nation like Singapore which is moving towards a sustainable, zero waste future, reuse of SIA in the construction industry is a potential area to explore. This could possibly slow down the rapid filling of Semakau Landfill, reduce waste generated in the construction industry and reduce carbon emissions. This study aims to explore different treatment methods for SIA to improve heavy metal leaching and make it feasible to be used as green construction material. Three types of SIA, sludge bottom ash (SBA), sludge mixed ash (SMA) and sludge fly ash (SFA), were treated using water washing and chelation. Parameters such as duration, number of washing steps and liquid-to-solid (L/S) ratios were explored for washing. Three different chelating agents with varied concentrations were used for heavy metal removal. Batch leaching results for raw SIA showed that the leaching concentrations of Hg, Mo, As, Sb, F- and SO42- were exceeding EU Waste Acceptance Criteria (WAC). After performing four step washing with L/S ratio 10 L/kg, Hg was found to leach out significantly from SBA and hence SBA has to be classified hazardous based on EU WAC. Leaching of other elements namely Mo, Sb and F- were above EU WAC inert criteria. Leaching concentrations of Hg, Mo, F- and SO42- from SMA and Hg, Mo, Sb, F- and SO42- from SFA were above EU WAC inert criteria. Chelation using diethylenetriaminepentaacetic acid (DTPA) and nitrilotriacetic acid (NTA) were effective in extraction of heavy metals by forming water soluble complexes. Increase in reagent concentration resulted in increase in extraction amount of heavy metals. Sodium dimethyl dithiocarbamate (SDDC) was effective in stabilising heavy metals as it forms insoluble complexes with metal ions. Further research should be conducted to study the leaching performance of SIA. Different parameters and new treatment methods should be used to establish the most sustainable and economical treatment method for SIA so that it can be used as a replacement for traditional construction material.